Factors associated with bone mineral density in women who underwent bariatric surgery - Luzia Jaeger Hintze; Alexandre dos Santos Cremon; Cheila Aparecida Bevilaqua; Josiane Aparecida Alves Bianchini; Nelson Nardo Junior (Universidade Estadual de Maringá, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.14930 To analyze factors associated with bone mineral density (BMD) of candidates and patients admitted to Bariatric Surgery (BS). This study included 61 women who had done or were waiting for BS. Anthropometric variables, body composition and BMD from the femur, femoral neck, lumbar spine and the whole body were measured. The factors associated with changes in BMD, such as smoking, alcohol ingestion, sedentary lifestyle, BS, nutritional supplementation and age were evaluated. The statistical significance was set at 5%. Age and BS were associated with changes in BMD. Among the individuals who had  BS done, the rates of osteopenia/osteoporosis were greater in the femur (OR 3.34; CI [1.52 - 1.83]) and femoral neck (OR 3.69; CI [1.34 - 2.08]). Subjects older than 50 years also had greater rates of BMD in the lumbar spine (OR 4.12; CI [2.09 - 22.33]), the whole body (OR 4.77; CI [1.34 - 28.14]), femur (OR 16.94; CI [2.16 - 124.32]) and femoral neck (OR 14.95; CI [1.86 - 110.66]). Patients who have had BS and are over 50 years of age showed higher rates of osteopenia/osteoporosis, which demonstrate the necessity of further studies exploring the effects of BS and its impact on bone metabolism.